Los contenidos curriculares - Maris Vázquez, Sheila (Revista Española de Pedagogía, 2016)
This paper discusses the origin and the philosophical assumptions of the Spanish reform typology of contents, assumed by Argentine educational transformation in the 90s. It tries to show that the theses of social constructivism -rooted in Kantian idealism- and of psychological formalism, are still in force. The criterion of selection of curricular contents -social significance- is also discussed, attempting to show that the basic principles assumed by this criterion lead to relativization of pedagogical statements. The need to approach curricular theory from a metaphysical and anthropological foundation is proposed.
Keywords: Revista Española de Pedagogía